Odpowiedź :
Odpowiedź:
[tex]a)\ \ 9^5=(3^2)^5=3^{2\cdot5}=3^{10}\\\\b)\ \ 15^9:5^9=(15:5)^9=3^9\\\\c)\ \ 6^7\cdot0,5^7=(6\cdot0,5)^7=3^7\\\\d)\ \ \frac{3^8}{81}=\frac{3^8}{3^4}=3^{8-4}=3^4\\\\e)\ \ 27\cdot3^7=3^3\cdot3^7=3^{3+7}=3^{10}\\\\f)\ \ 9^6:3^5=(3^2)^6:3^5=3^{12}:3^5=3^{12-5}=3^7[/tex]
Odpowiedź:
Szczegółowe wyjaśnienie:
[tex]9^{5} = (3^{2})^{5} = 3^{10} \\15^{9} : 5^{9} = (15 : 5)^{9} = 3^{9} \\6^{7} * 0,5^{7} = (6 * 0,5)^{7} = 3^{7} \\\frac{3^{8} }{81} = \frac{3^{8} }{3^{4} } = 3^{4} \\\\27 * 3^{7} = 3^{3} * 3^{7} = 3^{10} \\9^{8} : 3^{5} = (3^{2})^{8} : 3^{5} = 3^{16} : 3^{5} = 3^{11}[/tex]